2007
DOI: 10.3390/s7040493
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of PZT Thick Films for Sensing and Actuation

Abstract: Lead Zirconate Titanate oxide (PZT) thick films with thicknesses of up to 10 µm were developed using a modified sol-gel technique. Usually, the film thickness is less than 1 µm by conventional sol-gel processing, while the electrical charge accumulation which reveals the direct effect of piezoelectricity is proportional to the film thickness and therefore restricted. Two approaches were adopted to conventional sol-gel processing -precursor concentration modulation and rapid thermal annealing. A 10 µm thick fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…6(b) and (c)). PZT film prepared with 0.25 molar ratio of DEA has the remanent polarization of 5.7 C cm −2 and coercive voltage of 16 V. This polarization value is highly significant giving due consideration for the high thickness of the film compared to similar studies [37]. As could be seen in Fig.…”
Section: Effect Of Deamentioning
confidence: 92%
“…6(b) and (c)). PZT film prepared with 0.25 molar ratio of DEA has the remanent polarization of 5.7 C cm −2 and coercive voltage of 16 V. This polarization value is highly significant giving due consideration for the high thickness of the film compared to similar studies [37]. As could be seen in Fig.…”
Section: Effect Of Deamentioning
confidence: 92%
“…The parameters of our sample are in the state of this art for screen printed device [13]. Moreover the coupling factor, the Curie temperature and the dielectric loss are on pair with a disc with the same PZT base [14].…”
Section: Measurementmentioning
confidence: 99%
“…Considering the fact that the system is a stack of different materials with different thicknesses and mechanical properties, the resonance frequencies of the whole device are a mix of the influence of the different elements that constitute it. Indeed substrate and electrodes play a role with the frequency response of the system [8]. However with a thicker deposited PZT layer it has been shown that the structure can overcome the influence of electrodes.…”
Section: Resonance Frequency Measurementmentioning
confidence: 99%